'Capable of being in uncertainties': applied medical humanities in undergraduate medical education. Issue 3 (27th September 2021) - Thacker, Neepa; Wallis, Jennifer; Winning, Jo
Abstract : Numerous medical schools have been updating and modernising their undergraduate curricula in response to the changing health needs of today's society and the updated General Medical Council competencies required for qualification. The humanities are sometimes seen as a way of addressing both of these requirements. Medical humanities advocates would argue that the humanities have a vital role to play in undergraduate medical education, allowing students to develop the critical tools required by the 21st-century clinician to deliver the best person-centred care. While we endorse this view, we contend that such training must be taught authentically to have maximal impact. This article arises from a collaboration between Imperial College London and Birkbeck, University of London, which aimed to embed the humanities into Imperial's undergraduate medical curriculum. Here, we use a teaching session on graphic medicine and narrative as a case study to illustrate how the humanities can be a powerful tool for students to explore professional clinical complexity and uncertainty when taught in a transdisciplinary way. In this session, uncertainty operated on several different levels: the introduction of unfamiliar concepts, materials, and methods to students, transdisciplinary approaches to teaching, and the complexities of real-life clinical practice. Further, we argue that to manage uncertainty, medical students must cross from a scientific training based on positivist understandings of evidence and knowledge, to one which foregrounds multiplicity, nuance, interpretive critical thinking, and which understands knowledge as contingent and contextually produced. In facilitating such learning, it is crucial that the teaching team includes experts from both medical and humanities fields to scaffold student learning in an intellectually dynamic way, drawing on their disciplinary knowledge and wide range of personal professional experiences.